2023
DOI: 10.3390/s23042321
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmography Signal Wavelet Enhancement and Novel Features Selection for Non-Invasive Cuff-Less Blood Pressure Monitoring

Abstract: In this paper, new features relevant to blood pressure (BP) estimation using photoplethysmography (PPG) are presented. A total of 195 features, including the proposed ones and those already known in the literature, have been calculated on a set composed of 50,000 pulses from 1080 different patients. Three feature selection methods, namely Correlation-based Feature Selection (CFS), RReliefF and Minimum Redundancy Maximum Relevance (MRMR), have then been applied to identify the most significant features for BP e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In a previous work carried out by the authors [29], PPG signals were analyzed to select the most significant features for BP estimation by using several selection algorithms, i.e., RReliefF [30,31], Correlation-based Feature Selection (CFS), and Minimum Redundancy Maximum Relevance (MRMR) [32,33]. That methodology has led to the justification of the application of the Maximal Overlap Discrete Wavelet Transform (MODWT) to enhance the single-site PPG signal and to the selection of new proposed features [29].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In a previous work carried out by the authors [29], PPG signals were analyzed to select the most significant features for BP estimation by using several selection algorithms, i.e., RReliefF [30,31], Correlation-based Feature Selection (CFS), and Minimum Redundancy Maximum Relevance (MRMR) [32,33]. That methodology has led to the justification of the application of the Maximal Overlap Discrete Wavelet Transform (MODWT) to enhance the single-site PPG signal and to the selection of new proposed features [29].…”
Section: Introductionmentioning
confidence: 93%
“…In a previous work carried out by the authors [29], PPG signals were analyzed to select the most significant features for BP estimation by using several selection algorithms, i.e., RReliefF [30,31], Correlation-based Feature Selection (CFS), and Minimum Redundancy Maximum Relevance (MRMR) [32,33]. That methodology has led to the justification of the application of the Maximal Overlap Discrete Wavelet Transform (MODWT) to enhance the single-site PPG signal and to the selection of new proposed features [29]. Following this line of research, in this paper, our focus is on the actual development of ML techniques to find the best algorithm to measure BP, showing the usefulness of the already analyzed features and, in particular, those selected by means of MRMR, including those obtained after the enhancement with MODWT.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…ECG signal, and the PPT estimation from the difference (ms) between the systolic peaks of the ECG and PPG signals (second derivative photoplethysmography (SDPPG)) [28] Recent research has shown a growing interest in developing novel approaches for monitoring blood pressure in epilepsy patients during seizures. However, these studies mainly relied on traditional blood pressure monitoring or ECG signals [29] to measure blood pressure [30,31], which can be uncomfortable for the patient and cannot provide continuous monitoring. Several recent research studies have investigated non-invasive methods for continuous blood pressure monitoring, but few have focused specifically on monitoring blood pressure during seizures [32,33].…”
Section: Nomenclature and Symbolsmentioning
confidence: 99%